‘Short Bars Crossed’ to Remodel the Entire Chest Wall in Children and Adolescents with Pectus Excavatum - ERMERAK, NEZİH ONUR; YÜKSEL, MUSTAFA (My University, 2024)
Background: The cross-bar technique of minimally invasive pectus excavatum (PE) correction remains underreported, which is especially true of pediatric patients. We therefore reviewed the experience of a Turkish and an Austrian center. An additional novelty characterizing both pediatric cohorts was the use of short bars. Methods: In a retrospective study, pediatric PE corrections involving ‘short bars crossed’ were analyzed for complications and intra-/postoperative outcomes. Cases with two or three bars were included, given that a horizontal third bar was placed whenever considered useful for upper-chest elevation. All bars were fitted with a single stabilizer near the surgical entry point. In the Austrian center, intercostal nerve cryoablation was used for pain management. Descriptive statistics are presented. Results: Seventy-eight patients ≤18 years old were evaluable at the Turkish (n = 56) and Austrian (n = 22) centers. Total median values were 16.2 (IQR: 15.1–17.4) years for age and 4.60 (IQR: 3.50–6.11) for Haller index. Ten mild or moderate complications (12.8%) were observed, including just one revision requirement due to bar migration (1.28%). Intercostal nerve cryoablation (n = 13) was associated with longer surgical procedures at 150 (IQR: 137–171) versus 80 (IQR: 60–100) minutes but with shorter hospital stays, given an IQR of 3–4 days versus 4–5 days. Conclusion: ‘Short bars crossed’—with a single stabilizer in a ventral position close to the surgical entry point—ensure a wide distribution of forces, protect against bar migration, are safe and effective, and offer stability at an age characterized by growth and physical activity. Level of Evidence: IV.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; PEDIATRICS; Cerrahi; Pediatri, Perinatoloji ve Çocuk Sağlığı; Surgery; Pediatrics, Perinatology and Child Health; Cross-bar technique; Entire chest wall repair; Minimally invasive repair of pectus excavatum; Pectus excavatum; Short-bar technique